2021
DOI: 10.15420/aer.2021.34
|View full text |Cite
|
Sign up to set email alerts
|

Residual Stroke Risk in Atrial Fibrillation

Abstract: AF contributes to increased stroke risk via various mechanisms, including deranged blood constituents, vessel wall abnormalities and abnormal blood flow. This excess risk is frequently managed with anticoagulation therapy, aimed at preventing thromboembolic complications. Yet, a significant proportion of patients with AF remain at high residual stroke risk despite receiving appropriate dose-adjusted anticoagulation. This article explores the residual stroke risk in AF and potential therapeutic options for thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 90 publications
0
11
0
Order By: Relevance
“…Using CARS and CHA 2 DS 2 -VASc score, patients with a high residual risk of ischaemic stroke despite treatment 18 , 19 may be identified for more intensive follow-up and holistic management strategies. Indeed, adherence to the guideline-recommended Atrial fibrillation Better Care (ABC) pathway is associated with a 45% reduction in ischaemic stroke, compared to non-adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Using CARS and CHA 2 DS 2 -VASc score, patients with a high residual risk of ischaemic stroke despite treatment 18 , 19 may be identified for more intensive follow-up and holistic management strategies. Indeed, adherence to the guideline-recommended Atrial fibrillation Better Care (ABC) pathway is associated with a 45% reduction in ischaemic stroke, compared to non-adherence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, real-world experience has indicated that adherence to anticoagulation is far from optimal, thereby leaving many patients unprotected [36,37]. (3) Even in patients with chronic anticoagulation using either warfarin or NOACs/ DOACs, a substantial risk of thrombus formation in the LAA remains despite medication compliance [35,[38][39][40][41]. Finally, (4) surgical approaches are invasive, thus making their widespread application inappropriate for most patients with AF; patients are additionally exposed to residual risks associated with remnants of the LAA or residual leakage regardless of the surgical exclusion method.…”
Section: Laao Devicesmentioning
confidence: 99%
“…As such, a proportion of patients with AF will suffer from residual ischemic stroke despite receiving adequate anticoagulation therapy. 7 Attention to other comorbidities is therefore recommended, as part of the holistic approach to AF care, 8 given the improved outcomes evident with adherence to such an approach. 9 …”
mentioning
confidence: 99%